Alcohol Consumption and Functional Limitations in Older Men: Does Muscle Strength Mediate Them?. Issue 11 (2nd August 2019) - Wang, Tong; Sun, Shuqin; Li, Suyun; Sun, Yanping; Sun, Yongye; Zhang, Dongfeng; Wu, Yili
Abstract : OBJECTIVES: To evaluate the dose‐response relationships between alcohol consumption and functional limitations in older European men, and explore the role of muscle strength as a mediator of these relationships. DESIGN: Cross‐sectional study of older men participating in the Survey of Health, Aging and Retirement in Europe (SHARE). SETTING: Urban and rural households in 17 European countries and Israel. PARTICIPANTS: A total of 17 870 men aged 65 years and older from the SHARE (Wave 6, 2015) were included in this study. MEASUREMENTS: Outcome variables were functional limitations: mobility limitation, arm function limitation, and fine motor limitation. Main exposure variable was alcohol consumption. Mediating factor was grip strength. Basic demographics, life habits, and health status were considered as potential confounders. Dose‐response analyses with restricted cubic splines and the Karlson/Holm/Breen method were conducted. RESULTS: A total of 17 870 participants were included in this study. Dose‐response analyses revealed that moderate alcohol consumption was related to the lower odds of reporting mobility limitation (≤35 units/wk) and arm function limitation (≤41 units/wk), with a minimum odds ratio (OR) occurring at 10 units/week drinks for mobility limitation (OR = .71; 95% confidence interval [CI] = .62‐.81) and arm function limitation (OR = .66; 95% CI = .59‐.75). The odds of reporting the fine motor limitation monotonically increased with alcohol consumption when alcohol consumption was beyond 15 units/week. No significant mediating effect of grip strength on the relationships between alcohol consumption and mobility limitation and arm function limitation was found. CONCLUSION: Moderate alcohol consumption has a protective role in mobility and arm function limitation in older European men. Grip strength is not the main mediator of these associations, suggesting that the protective effect is independent of muscle strength. Alcohol consumption is associated with higher odds of reporting fine motor limitation in older European men. J Am Geriatr Soc 67:2331–2337, 2019